A study on the corrosion of reinforcing bars in alkali-activated fly ash mortars under wet and dry exposures to chloride solutions. (September 2016) - Monticelli, C.; Natali, M.E.; Balbo, A.; Chiavari, C.; Zanotto, F.; Manzi, S.; Bignozzi, M.C.
Abstract: This research investigates the corrosion protection afforded to the embedded rebars by room temperature-cured alkali-activated mortars, based on class F fly ash (FA), during wet and dry (w/d) exposures to 0.1 M NaCl solution. The results were compared to those obtained in a traditional cement-based mortar (REF). The rebar corrosion behaviour was characterized by corrosion potentials (Ecor ) and potentiostatic polarization resistance (Rp ) measurements, polarization curve recording and electrochemical impedance spectroscopy (EIS). The information collected suggested that FA mortars afforded a lower corrosion protection to the rebars and the reason was investigated by microstructural, physical–mechanical and chemical analyses of the mortars. FA mortars were found to undergo a fast carbonation, so that depassivation of the rebars occurred concurrently, in spite of a limited total chloride content inside these mortars. REF mortar was much less susceptible to carbonation and rebar corrosion started when a sufficiently high chloride concentration was built up.